On the Optimization of Point Absorber Buoys - Linnea Sjökvist; Remya Krishna; Magnus Rahm; Valeria Castellucci; Hagnestål Anders; Mats Leijon (Journal of Marine Science and Engineering, 2014)
A point absorbing wave energy converter (WEC) is a complicated dynamical system. A semi-submerged buoy drives a power take-off device (PTO), which acts as a linear or non-linear damper of the WEC system. The buoy motion depends on the buoy geometry and dimensions, the mass of the moving parts of the system and on the damping force from the generator. The electromagnetic damping in the generator depends on both the generator specifications, the connected load and the buoy velocity. In this paper a velocity ratio has been used to study how the geometric parameters buoy draft and radius, assuming constant generator damping coefficient, affects the motion and the energy absorption of a WEC. It have been concluded that an optimal buoy geometry can be identified for a specific generator damping. The simulated WEC performance have been compared with experimental values from two WECs with similar generators but different buoys. Conclusions have been drawn about their behaviour.